2005
DOI: 10.1037/1064-1297.13.4.319
|View full text |Cite
|
Sign up to set email alerts
|

Effects of repeated-dose isradipine on the abuse liability of cocaine.

Abstract: Despite preclinical studies suggesting that isradipine may antagonize the abuse liability of cocaine, pretreatment with sustained-release isradipine did not reduce euphoric mood in cocaine-using volunteers. This double-blind, within-subject, crossover laboratory study determined whether maximal dose-loading with isradipine could antagonize effects of cocaine in 12 cocaine-dependent research volunteers administered intravenous cocaine doses (0, 0.325, and 0.65 mg/kg) on different days after 5 days of treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 26 publications
1
28
0
Order By: Relevance
“…Some results have been considered particularly encouraging; for example, an LCCBmediated increased the ability to refuse further doses of methamphetamine (Johnson et al, 1999). However, LCCBs have also been reported to enhance some subjective effects of abused drugs (Vaupel et al, 1993;Roache et al, 2005). The explanation for these mixed results is unclear, since divergent results have been seen even in studies examining drug-dependent individuals with a double-blind design.…”
Section: L-type Calcium Channels: Human Studiesmentioning
confidence: 99%
“…Some results have been considered particularly encouraging; for example, an LCCBmediated increased the ability to refuse further doses of methamphetamine (Johnson et al, 1999). However, LCCBs have also been reported to enhance some subjective effects of abused drugs (Vaupel et al, 1993;Roache et al, 2005). The explanation for these mixed results is unclear, since divergent results have been seen even in studies examining drug-dependent individuals with a double-blind design.…”
Section: L-type Calcium Channels: Human Studiesmentioning
confidence: 99%
“…As summarized in Table III, conflicting results have been reported in preliminary clinical studies examining stimulants' abuse liability in humans [Muntaner et al, 1991;Rosse et al, 1994;Fabian and Silverstone, 1997;Johnson et al, 1999Johnson et al, , 2004Johnson et al, , 2005bMalcolm et al, 1999;Gottschalk and Kosten, 2002;Sofuoglu et al, 2003;Roache et al, 2005]. Roache et al [2005] suggested that isradipine could even increase subjective effects and reinforcement caused by cocaine use.…”
Section: Psychostimulantsmentioning
confidence: 99%
“…Roache et al [2005] suggested that isradipine could even increase subjective effects and reinforcement caused by cocaine use. On the contrary, some positive findings have been published for isradipine in methamphetamine addicts [Johnson et al, 2005a].…”
Section: Psychostimulantsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used it in previous studies demonstrating reliable dose-related cocaine effects amenable to alteration by putative treatment agents (Johnson et al . 2004, 2007a; Roache et al . 2005).…”
Section: Methodsmentioning
confidence: 99%